PERANAN SEKTOR BASIS TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) KABUPATEN SAROLANGUN TAHUN 2001-2012 - Andi Ayu Puji Lestari (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2016)
The title of this thesis is the Role of the Base Sector in Increasing Regional Original Income (PAD) of Sarolangun Regency for the 2001-2012 period under the guidance of Dr. Junaidi, SE., M.Sc. The purpose of this research is to analyze the development of PAD in Sarolangun Regency, to analyze the basic sector in the economy of Sarolangun Regency and to analyze the role of the base sector in increasing PAD in Sarolagun Regency 2001-2012. The method used to answer the problems in this study is the Location Quotient (LQ) analysis and regression analysis. The results of this study show that the development of PAD in Sarolangun Regency for the period 2001-2012 averaged 25.9 percent. Obtained 3 (three) base sectors, namely the agricultural sector, mining sector and trade sector with LQ values ​​> 1. Using a simple regression model it was obtained that the basis sector had a positive and significant effect on PAD in Sarolangun Regency.